Prioritizing EU Projects by Using Decomposed Fuzzy AHP and TOPSIS - Onar, Sezi Cevik; Cebi, Selcuk; Oztaysi, Basar; Kahraman, Cengiz (OLD CITY PUBLISHING INC, 2024)
Research funds are critical for companies since they play a crucial role in fostering innovation, growth, and competitiveness. European Union (EU) leads innovation and research by publishing research calls in various areas. For companies planning to apply for calls, it is important to make an assessment and apply for calls after prioritization. In this study, we propose a fuzzy decision-making approach that firms can use to evaluate project calls. This approach utilizes a novel extension of ordinary fuzzy approach, the DFS based Analytic Hierarchy Process (AHP) is used to determine the weights of the criteria, and then DFS based TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) is used to determine the priorities of the projects. To demonstrate the performance of the proposed approach, it is applied for prioritizing EU project calls. In the case study, a decision model including seven criteria and eight alternative projects was handled, and the projects were prioritized. The results reveal that the proposed approach provides an objective and robust prioritization model.
Keywords: Decomposed Fuzzy Sets; EU Projects; AHP; TOPSIS; Prioritization; SELECTION; METHODOLOGY; Computer Science; Science & Technology - Other Topics